Petualangan Intelektual al-Ghazali dan Sardar dalam Mencari Kebenaran - Asari, Hasan (Program Pascasarjana UIN Sunan Ampel Surabaya, 2009)
For the real intellectuals, truth is a search, a journey, a couse, an endeavor. They believe that truth can only be attained through series of painstaking process. The autobiographies of al-Ghazâlî and Sardar are fine illustrations of this kind of search for thruth. Although al-Ghazâlî and Sardar are separated by ten centuries, one can find clear parallels in antomy and procedures of their journeys in seeking truth. The present author attempts to analyse these autobiographies and shows why they could be a good example for young intellectuals.